1985
DOI: 10.1002/j.1460-2075.1985.tb04057.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a set of genes expressed during the G0/G1 transition of cultured mouse cells.

Abstract: To identify previously undetected genes that may be involved in the transition from a resting state (G0) to a proliferative state (G1) of mammalian cells, we set out to isolate cDNA clones derived from mRNAs that appear in serum‐stimulated cells in the absence of protein synthesis. A lambda cDNA library was prepared using poly(A)+ RNA from BALB/c 3T3 cells that had been brought to quiescence and subsequently stimulated with serum in the presence of cycloheximide. Approximately 50 000 recombinant phage plaques … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
349
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 581 publications
(363 citation statements)
references
References 47 publications
12
349
0
1
Order By: Relevance
“…We therefore postulated that ATRA stimulation of pgrn mRNA expression would not be mediated through direct actions on the GRN promoter but would be a secondary action of ATRA requiring intermediate gene induction and de novo protein synthesis. This was investigated using CHX, a protein synthesis inhibitor (32). In ATRA-stimulated HL-60 cells, CHX suppressed the upregulation of the pgrn transcript, whereas CHX on its own had no effects (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore postulated that ATRA stimulation of pgrn mRNA expression would not be mediated through direct actions on the GRN promoter but would be a secondary action of ATRA requiring intermediate gene induction and de novo protein synthesis. This was investigated using CHX, a protein synthesis inhibitor (32). In ATRA-stimulated HL-60 cells, CHX suppressed the upregulation of the pgrn transcript, whereas CHX on its own had no effects (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this notion, several recent investigations have shown that MAP kinase specific phosphatase-1 (MKP-1) deficiency results in enhanced and prolonged p38 and JNK activation (Nimah et al, 2005;Wu and Bennett, 2005;Zhao et al, 2005). MKPs were initially identified as early response genes (Lau and Nathans, 1985;Sun et al, 1993) and are expressed ubiquitously in response to growth factors, stress, or heat shock (Farooq and Zhou, 2004;Chi et al, 2006;Hammer et al, 2006). They are known to play a regulatory role in the production of pro-or anti-inflammatory cytokines following stimulation with LPS, peptidoglycan, or dexamethasone (Hammer et al, 2005;Chi et al, 2006).…”
Section: Introductionmentioning
confidence: 81%
“…The matching expression and binding pattern suggest that WISP-1 interacts with the surface of its expressing cells. Other members of the CCN family including WISP-2, CTGF, and Cyr61 are also expressed by fibroblasts (4,26,27). Moreover, CTGF and Cyr61 remain associated with the extracellular matrix and the cell surface upon secretion (26,28,29).…”
Section: Wisp-1 Binds To Decorin At the Surface Of Human Skinmentioning
confidence: 99%